Antimicrobial peptide-conjugated graphene oxide membrane for efficient removal and effective killing of multiple drug resistant bacteria. Issue 24 (15th March 2015) - Kanchanapally, Rajashekhar; Viraka Nellore, Bhanu Priya; Sinha, Sudarson Sekhar; Pedraza, Francisco; Jones, Stacy J.; Pramanik, Avijit; Chavva, Suhash Reddy; Tchounwou, Christine; Shi, Yongliang; Vangara, Aruna; Sardar, Dhiraj; Ray, Paresh Chandra
<x xml:space="preserve">Abstract</x> An antimicrobial peptide conjugated 3D graphene oxide membrane has the ability to separate, identify and disinfect MRSA from water.